Effects of synbiotics containing Bifidobacterium animalis subsp. lactis GCL2505 and inulin on intestinal bifidobacteria: A randomized, placebo‐controlled, crossover study. Issue 5 (21st April 2019) - Anzawa, Daisuke; Mawatari, Takashi; Tanaka, Yoshiyuki; Yamamoto, Mio; Genda, Tomomi; Takahashi, Shota; Nishijima, Tomohiko; Kamasaka, Hiroshi; Suzuki, Satoru; Kuriki, Takashi
Abstract: A number of studies have shown the bifidogenic effects of either probiotic bifidobacteria or inulin, and this bifidogenic shift in the composition of the colonic microbiota is likely the basis for their positive impact on human health. This study aimed to evaluate the effects of synbiotics containing the probiotic bacterium Bifidobacterium animalis subsp. lactis ( B. lactis ) GCL2505 and inulin on the levels of intestinal bifidobacteria compared with B. lactis GCL2505 alone. A randomized, double‐blind, placebo‐controlled, crossover trial was carried out involving 60 healthy subjects with a tendency for constipation using fermented milk containing B. lactis GCL2505 and inulin (synbiotic), only B. lactis GCL2505 (probiotic), and placebo. Fecal samples were collected at the end of each 2‐week intervention period, and the bifidobacterial count was analyzed by quantitative real‐time PCR. The numbers of total bifidobacteria and B. lactis in feces were significantly increased during the probiotic and synbiotic intake periods compared with the placebo intake period. Furthermore, the numbers of total bifidobacteria and endogenous bifidobacteria were significantly higher in the synbiotic intake period compared with the probiotic intake period, while there was no difference in the number of B. lactis . These results suggested that the synbiotics containing B. lactis GCL2505 and inulin had a greater effect on the number of bifidobacteria than a drink containing probiotics alone and could be useful for the improvement of the intestinal environment. Abstract : Consumption of synbiotics containing Bifidobacterium animalis subsp. lactis GCL2505 and inulin had a greater effect on the number of bifidobacteria than the probiotics alone. This synbiotics was also effective in subjects who had a relatively small increase of B. lactis after the ingestion of B. lactis GCL2505 alone.